Comparative Efficacy of 6 Topical Pharmacological Agents for Preventive Interventions of Postoperative Sore Throat After Tracheal Intubation: A Systematic Review and Network Meta-analysis - Wang, Ge; Qi, Yang; Wu, LiNa; Jiang, GuiChun (Anesthesia and analgesia, 2021)
Topical pharmacological agents typically used to treat postoperative sore throat (POST) after tracheal intubation include nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids, lidocaine, Glycyrrhiza (licorice), and N-methyl-d-aspartate (NMDA) receptor antagonists (including ketamine and magnesium). However, the optimal prophylactic drug remains elusive. The literature published before September 8, 2019 was searched on the PubMed, the Embase, the Web of Science, and the Cochrane Library. Randomized controlled trials (RCTs) covering topical prophylactic medications for patients with POST were included. Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was used to assess the quality of evidence. The primary outcome is the risk of POST. Combining both direct and indirect evidence, a network meta-analysis was performed to assess odds ratios (ORs) between the topical pharmacological agents and surface under the cumulative ranking (SUCRA) curve for the treatment-based outcomes. This study is registered with PROSPERO, number CRD42020158985. Sixty-two RCTs (at least 73% of which were double blinded) that included a total of 6708 subjects and compared 6 categories of drugs and/or placebos were ultimately enrolled. All preventive interventions except lidocaine were more effective than placebo at the 4 time intervals. Lidocaine (OR: 0.35, 95% credible interval [CrI], 0.16-0.79) has a greater POST preventative intervention effect than the placebo at a time interval of only 2 to 3 hours after surgery. Relative to lidocaine, the risk of POST except 2 to 3 hours was lower for the following treatments: corticosteroids, ketamine, magnesium, NSAIDs, and Glycyrrhiza. The NMDA receptor antagonists studied here included ketamine and magnesium. Magnesium generally demonstrated greater benefit than ketamine at 24 hours postsurgery/extubation (OR: 0.41, 95% CrI, 0.18-0.92). Compared with ketamine, corticosteroids were associated with a reduced risk of POST during the 4 to 6 hours (OR: 0.40, 95% CrI, 0.19-0.83) and 24 hours (OR: 0.34, 95% CrI, 0.16-0.72) time intervals. During the 2 to 3 hours time interval, Glycyrrhiza (OR: 0.38, 95% CrI, 0.15-0.97) was more efficacious than magnesium. Our analysis shows that, among the 6 topical medications studied, lidocaine is not optimal for topical use to prevent POST. Glycyrrhizin, corticosteroids, NSAIDs, and NMDA receptor antagonists (ketamine and magnesium) are associated with a reduced postoperative pharyngeal pain across the 4 postsurgical time intervals studied, all of which can be chosen according to the clinical experience of the anesthesiologists and the patient preferences and are recommended for the reduction of postoperative throat pain.